Structural carbon-carbon materials for accelerator-driven systems - Gurin, V.A.; Bakai, A.S.; Gurin, I.V.; Omelchuk, A.A.; Buryak, M.I.; Voronin, B.M.; Shmehera, R.S. (Вопросы атомной науки и техники, 2005)
The paper presents results of investigations of the compatibility of carbon-carbon composite materials with molten sodium fluoride – zirconium fluoride mixture in the presence of molten lead and its fluoride. The investigations have been carried out both without irradiation and with irradiation with an electron beam of 10 MeV energy and 5 kW power (current density 0.5 mA/cm2) on a linear electron accelerator LPE–10 (LINAC–10). It has been shown that this material is impermeable to the above compounds. Does not interact with them. And does not break down on temperature cycling from room temperature to 700 °C. The mechanical properties of carbon-carbon composites have been investigated by the nanoindentation method. It has been found that neither long contact with molten fluoride mixture nor irradiation affects the mechanical properties of this material. Приведені результати досліджень сумісності вуглець-вуглецевих композиційних матеріалів з розплавленою сумішшю фторидів натрію та цирконію в присутності розплавленого свинцю та його фториду. Дослідження виконані як без опромінення, так і при опроміненні пучком електронів енергією 10 МеВ та потужністю 5 кВт (густина струму 0,5 мА/см 2 ) на лінійному прискорювачі електронів ЛПЕ –10 (LINAC-10). Показано, що даний матеріал в інертній атмосфері є непроникним для зазначених вище сполук, не взаємодіє з ними та не руйнується при термоциклюванні від кімнатної температури до 700 °С. Методом наноіндентування досліджені механічні властивості вуглець-вуглецевих композитів. Встановлено, що ні тривалий контакт з розплавленою фторидною сумішшю, ні опромінення не впливають на його механічні властивості. Приведены результаты исследований совместимости углерод-углеродных композиционных материалов с расплавленной смесью фторидов натрия и циркония в присутствии расплавленного свинца и его фторида. Исследование выполнены как без облучением так и при облучении пучком электронов энергией 10 МэВ та мощностью 5 кВт (плотность тока 0.5 мА/см 2 ) на линейном ускорителе электронов ЛУЭ – 10 (LINAC–10). Показано, что данный материал в инертной атмосфере является непроницаемым для указанных выше соединений, не взаимодействует с ними и не разрушается при термоциклировании от комнатной температуры до 700 °С. Методом наноиндентирования изучены механические свойства углерод-углеродных композитов. Определено, что ни долгий контакт с расплавленной фторидной смесью, ни облучение не влияют на его механические свойства